Statistical analysis of the strength reliability of the MAX phases. Issue 2 (27th October 2022) - Yin, Hang; He, Xiaodong; Song, Guangping; Zheng, Yongting; Bai, Yuelei
Abstract: A good comprehension of the mechanical property stability is crucial in promoting the structural applications of the MAX phases. This study aims to determine the most suitable intensity distribution for the experimental flexural strength of present Ti3 AlC2 and previous Ti3 SiC2, optimize the fitting parameters, and explore the error sources. After comparing two‐parameter Weibull, three‐parameter (3P) Weibull, and other three distributions, the 3P‐Weibull distribution is the most suitable for the MAX phases. The different parameter estimation methods, rank estimators, and minimum used sample numbers of 3P‐Weibull were tested to determine safe and accurate parameter values for engineering application. Furthermore, the 3P‐Weibull modulus (2.32 for Ti3 AlC2 and 2.04 for Ti3 SiC2 ) indicates that the MAX phases occupy a middle ground between typical metals and ceramics, attributing to their high fracture toughness and the R ‐curve behavior. These findings would open up prospects for the standardization of testing methods for the Weibull statistics of the MAX phases.